Role-Playing Activities in Improving Responsibility among Children Aged 5–6 Years: A Classroom Action Research - Nur Lailatul Farcha; Henni Anggraini; Mochamad Ramli Akbar (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
This study aimed to improve responsibility among children aged 5–6 years through role-playing activities at Baitul Muchlisin Kindergarten. The research employed Classroom Action Research (CAR) based on the cyclical model consisting of planning, action, observation, and reflection stages. The participants involved 16 children aged 5–6 years in Group B. The study was conducted in two cycles, with each cycle consisting of two meetings designed to enhance children’s responsibility, particularly in maintaining personal hygiene, following classroom routines, and completing simple tasks independently. Data were collected through observation, documentation, field notes, and assessment rubrics using qualitative and quantitative descriptive approaches. The intervention implemented “teacher–student” role-playing scenarios in which children alternated roles as teachers and students in simulated classroom situations related to personal hygiene and responsible behavior. Reflection results from Cycle I indicated that children still required considerable teacher guidance; therefore, Cycle II integrated additional learning supports, including role cards, hygiene posters, mirrors, personal hygiene tools, praise, and reward stickers to increase participation and independence. Quantitative findings demonstrated a significant improvement in responsibility scores from 50.19% in Cycle I to 91.02% in Cycle II. Qualitative findings further revealed improvements in children’s confidence, independence, participation, and awareness in maintaining personal hygiene and encouraging peers to practice clean habits. These findings indicate that role-playing activities effectively strengthen responsibility and character development in early childhood education.